Pelaksanaan Program Surabaya Mengajar Angkatan 7 SDN Manukan Kulon VI Kecamatan Tandes Kabupaten Surabaya - Yulianti Tri Pratiwi; Nonik Indrawatiningsih (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The Surabaya Mengajar Batch 7 Program aims to study the profile of SD Negeri Manukan Kulon VI, the vision and mission implemented, the organizational structure and work procedures of the school, the culture and values ​​adopted, the activities of general and special teachers, the student learning process, and formal ceremonial activities. The Surabaya Mengajar Batch 7 Program will run from February to June 2025. The purpose of this program is to provide teaching experience, broaden horizons, training and development of skills, independence, responsibility, and the ability to develop professionalism in the field of teaching or education. The program will also provide opportunities for students to apply their own discoveries. At SD Negeri Manukan Kulon VI, the Surabaya Mengajar Batch 7 Program runs from September 10 to June 2, 2024. To start the Surabaya Mengajar Program work program, observations were carried out both physically and non-physically to see how the school looks as a whole, including facilities, infrastructure, teaching materials, and other learning equipment. Based on the results of the observations, a schedule was made for the preparation and implementation of the Surabaya Mengajar Program. With the Surabaya Mengajar Program at SD Negeri Manukan Kulon VI, students can improve their teaching skills, implement activity programs that aim to optimize the potential in schools, provide opportunities for students to learn and recognize problems in schools related to the learning process and school administration, and exchange knowledge, skills, and attitude values ​​that have been learned in real life at school.